Pengaruh Leverage, Pertumbuhan Perusahaan, Ukuran Perusahaan, Risk Profile dan Profitabilitas Terhadap Nilai Perusahaan - Kadek Meilyana Syahrani; Luh Komang Merawati; Daniel Raditya Tandio (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
This study aims to determine and test the effect of leverage, growth, size, risk profile, and profitability, on firm value in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The research population is banking companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The sample in this study were 41 banking companies which were determined based on the purposive sampling method. The analysis technique used in this study is multiple linear regression analysis. Based on the results of the study, it shows that leverage has no effect on firm value, growth has a positive effect on firm value, size has a positive effect on firm value, risk profile has no effect on firm value, and profitability has a positive effect on firm value.